Harmonics analysis of industrial and commercial distribution networks with high penetration of power electronics converters - Zare, Firuz; Kumar, D. (2016)
© 2016 IEEE. This paper presents harmonic analysis of grid connected three-phase power electronics converters utilized in commercial and industrial distribution networks. Different threephase power converters topologies and configurations have been analysed in a low voltage distribution network in order to estimate harmonics emissions of the system. Analyses and mathematical modelling have been verified by simulation results.